2019
DOI: 10.4236/jmmce.2019.71003
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Mechanical Properties of Impact Modified Polyvinyl Chloride-Fly Ash Composites

Abstract: The mechanical properties like tensile, pin bearing and impact properties have been studied for composites containing Fly Ash (FA) and Impact modifier (IM) in Polyvinyl Chloride (PVC) for furniture and pipe applications. Pin-bearing test is an important tool to evaluate the ability of the material to retain fasteners and the ability of the material to sustain load during the service life. The present paper evaluates the effect of variation of FA and IM on the pin bearing strength, tensile strength, modulus elo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…They reported that FA fillers with smaller particles result in better interfacial interaction and improved properties. In their other studies, 14,18,19 they observed that mechanical strength, stiffness, viscoelastic, and thermal properties increased with the addition of FA fillers into the PVC polymer matrix. Islam et al 21 studied the electrical and tensile behavior of CB reinforced PVC conductive composites.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…They reported that FA fillers with smaller particles result in better interfacial interaction and improved properties. In their other studies, 14,18,19 they observed that mechanical strength, stiffness, viscoelastic, and thermal properties increased with the addition of FA fillers into the PVC polymer matrix. Islam et al 21 studied the electrical and tensile behavior of CB reinforced PVC conductive composites.…”
Section: Introductionmentioning
confidence: 91%
“…12,13 However, the mechanical properties are actually lower than desired. 14,15 In addition, fillers such as talc, fly ash (FA), carbon black (CB), and titanium dioxide are generally used in PVC polymer applications as well. Many studies have attempted to improve the mechanical properties and toughness of PVC polymers by the addition of calcium carbonate, 2,3,7,12,13 talc, 16,17 FA, 14,[18][19][20] CB, [21][22][23] titanium dioxide, 24 silicone dioxide, 25 and glass beads (GBs) [26][27][28] fillers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation